Water-Jet Erosion of Grade-A Ship Steel: Experimental Research. (10th March 2021) - Cao, Yupeng; Zhang, Yue; Shi, Weidong; Lu, Hua; Tan, Linwei; Yang, Yongfei
Abstract : A water-jet erosion test was carried out on grade-A ship steel to study the interaction and erosion mechanism of the water jet on the steel surface. When the water jet impacted, a STSS-1 stress-detection module was used to collect the dynamic strain signal on the rear of the ship's plate, and a scanning electron microscope, transmission electron microscope, X-ray diffractometer, and other equipment were used to analyze the microstructure and phase of the grade-A ship steel before impact. The surface morphology of the material after impact was studied and analyzed. The impact stress of the water jet on the grade-A steel was an alternating stress, and the jet pressure decayed in the radial direction. The material surface was fatigued under the action of the jet alternating stress. After the water-jet erosion, the central area of the grade-A steel was dominated by an elongated cementite hard phase, and the peripheral area had a pearlite structure. A model for the jet erosion and peeling of grade-A ship steel was established to clarify the mechanism of erosion by the water jet.